Cuantificación de metales pesados (plomo y cadmio) en agua, por Espectroscopía de Absorción Atómica con Horno de Grafito - Castillo Ayala, Jorge Enrique (Universidad Santiago de Cali, 2020)
The validation of lead and cadmium is presented by atomic absorption spectroscopy and atomization by graphite furnace as a means for the determination of these metals in drinking water and the crude of an aqueduct. The parameters evaluated were linear range (Lead: 1.0 and 10.0 μg/L and in cadmium is 0.1 to 2.0 μg/L), detection and quantification limits are of 0.3064 and 0.4759 μg/L for lead and for cadmium 0.0509 and 0.0814 μg/L respectively, the values corresponding to the calibration curves of the blanks method. The accuracy of the system was calculated by repeatability and reproducibility, which generated RSD less than 10%. The accuracy was calculated by the percentage of recovery with samples doped for lead of 2.5 and 8.0 μg/L and for cadmium with doped samples of 0.4, 1.0 and 1.5 μg/L. The aqueduct waters are not published lead and cadmium outside the regulations.